UNESCO world heritage branding: learning from some cases in Asia - Widodo, Johannes (Institute for Advanced Science Social, and Sustainable Future, 2023)
UNESCO World Heritage listing is often misunderstood as branding to promote mass tourism or as a vehicle for economic development by a city or the state party. The reflection is aimed to shed light on the fundamental principles that underlie the listing and the integration of the World Heritage scheme with the Sustainable Development Policy. The reflection is done through the case study method of a specific real-life phenomenon in Asia to gain insights into complex and intricate situations and highlight the common misunderstanding through several cases. The study found the policy bias towards investment and tourism agenda and not towards the fulfilment of public welfare, often without ethics applying the top-down policy. The study also found evidence of irreversible damages to tangible and intangible aspects of cultural and natural heritage due to gentrification, commodification, decreasing carrying capacity, and loss of authenticity. The study aims to understand better the four pillars of integrating the World Heritage and Sustainable Development policy in achieving environmental sustainability, inclusive social development, inclusive economic development, and fostering peace and security.